2018
DOI: 10.1590/1413-785220182604192681
|View full text |Cite
|
Sign up to set email alerts
|

Extra-Abdominal Desmoid Tumor: Analysis of 23 Consecutive Cases in a Single Institution

Abstract: Objective:Extra-abdominal desmoid tumor (EDT) is a rare condition, caused by proliferation of fibroblasts. Despite being a benign tumor, it is locally aggressive and has unpredictable clinical behavior. The objective of this study is to present the clinical outcomes of patients with EDT treated surgically between 1995 and 2016.Methods:This is a retrospective series of 23 patients with histopathological diagnosis of EDT that underwent surgery at the orthopedic oncology service of our hospital. The information w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
0
0
3
Order By: Relevance
“…Our results in terms of location seem to concur with several series and literature reviews, with a predominance in the extremities in over 50% of patients [ 8 ], whereas other case series place abdominal locations in the first position [ 4 , 12 ]. We have no clear explanation for this discrepancy in the literature, but it has been suggested that age may play a role in determining tumor site [ 4 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our results in terms of location seem to concur with several series and literature reviews, with a predominance in the extremities in over 50% of patients [ 8 ], whereas other case series place abdominal locations in the first position [ 4 , 12 ]. We have no clear explanation for this discrepancy in the literature, but it has been suggested that age may play a role in determining tumor site [ 4 ].…”
Section: Discussionsupporting
confidence: 91%
“…Reporte de un caso. Cir Gen. 2021; 43 (3): 176-180. https:// dx.doi.org/10.35366/108570 INTRODUCCIÓN L a fibromatosis desmoide, también conocida como tumor desmoide o fibromatosis agresiva, es una condición rara con una frecuencia de dos a cinco casos por millón de habitantes al año; [1][2][3] se caracteriza por la proliferación de fibroblastos, los cuales, a pesar de no tener características histológicas de malignidad, son agresivos a nivel local y con un comportamiento clínico impredecible; 2,3 la Organización Mun-dial de la Salud (OMS) la describe como una proliferación monoclonal de fibroblastos que afecta tejidos blandos con crecimiento infiltrante y con tendencia a la recurrencia local, pero sin presentar metástasis a distancia. 4 Este tipo de tumores se presenta en pacientes de entre 20 y 70 años de edad, y tiene un pico en su frecuencia entre los 30 y 40 años.…”
Section: -Year-old Female Patient Who Started With Pain In the Right ...unclassified
“…4 Este tipo de tumores se presenta en pacientes de entre 20 y 70 años de edad, y tiene un pico en su frecuencia entre los 30 y 40 años. 2,4 Según su localización se dividen en extraabdominal, de la pared abdominal o intraabdominal; de los extraabdominales, 17% se www.medigraphic.org.mx ubican en la cintura escapular. 3 El tratamiento de elección es la resección quirúrgica, que es un reto quirúrgico debido a la dificultad para distinguir la cápsula del tumor y por el alto riesgo de lesión al plexo braquial y vasos axilares, 1-3 además, por dichos factores se pueden necesitar múltiples procedimientos quirúrgicos y causar severa morbilidad estética y funcional, por lo cual la toma de decisión es compleja en este tipo de casos.…”
Section: -Year-old Female Patient Who Started With Pain In the Right ...unclassified
See 1 more Smart Citation
“… 9 Moreover, there is limited information regarding the clinical presentation and treatment patterns and outcomes of patients treated in Brazilian centers. 10 The disparities in treatment access among patients in developing countries is well known and it may be more prominent in patients diagnosed with rare cancers and sarcomas as demonstrated by a large cancer database study conducted in Brazil. 9 …”
Section: Introductionmentioning
confidence: 99%